Optimization of Corruption Prevention Government Procurement of Goods and Services - M. Haikal Aditya; Bella Vinia Ginting; Iklilah Dini Fajriyah; Yenni J Rammanda; Neng Sri Wardhani (International Journal of Economic Research and Financial Accounting, 2024)
The procurement of charcoal and services is an important aspect of clean and effective governance. This procurement process aims to meet the needs of public infrastructure, complement government facilities, and ensure the controlled use of state finances. However, in its implementation, there are often irregularities and corrupt practices that are detrimental to the State's finances. This study aims to analyze the factors that cause corruption in government procurement of goods and services, identify gaps in the system that are vulnerable to corrupt practices, and evaluate existing policies and regulations. The results of the analysis show that transparency, strengthening regulations, strict law enforcement, increasing the professionalism and integrity of procurement apparatus, and community participation in supervision are key steps in eradicating corruption in government procurement.  The implementation of good governance principles, including through the implementation of E-Government, is also an effective solution in overcoming corrupt practices. The results of the research are expected to provide concrete recommendations for improving the government procurement system for goods and services, improving the supervision mechanism, and strengthening integrity in the procurement process.